Decision Support System for Extending PT Nitro Pratama Indonesia Outlet Cooperation Using the Fuzzy AHP-TOPSIS - Radhyana Gayatri Faradilla; Rizka Hadiwiyanti; Abdul Rezha Efrat Najaf (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The increasingly competitive business environment required companies to make objective decisions, particularly in determining the feasibility of outlet contract extensions. PT Nitro Pratama Indonesia previously conducted this process manually, which often led to inconsistent decisions. This study aimed to develop a web-based decision support system to evaluate outlet cooperation systematically. A combination of Fuzzy Analytical Hierarchy Process (Fuzzy AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied. Fuzzy AHP was used to determine the weight of criteria under uncertain conditions, while TOPSIS was used to rank alternatives based on their proximity to the ideal solution. The study involved 50 active outlets located in Surabaya and Solo branches. The final criteria weights obtained were Outlet Revenue (0.33), Rental Cost (0.26), Outlet Location (0.16), Accessibility (0.11), Competitiveness (0.08), and Operational Cost (0.06). The ranking process generated objective recommendations that were consistent with manual calculations. Functional testing using Black Box Testing indicated that all system features operated properly. The system proved effective and relevant in supporting accurate and efficient decision-making for outlet contract extensions.